Change of motor abilities, including shot accuracy, in soccer players - Kubacki, Rafał; Buśko, Krzysztof (Journal of Education, Health and Sport, 2017)
Celem pracy było porównanie zmian wybranych cech motorycznych, w tym celności, u piłkarzy nożnych po pierwszej rundzie rozgrywek. W badaniach udział wzięło 13 piłkarzy nożnych z klubu KP „Polonia” Bydgoszcz. Charakterystyka badanych: wiek 24,9 ± 6,4 lat, wysokość ciała 177,5 ± 4,8 cm, masa ciała 76,2 ± 8,8 kg, staż treningowy 15,5 ± 6,6 lat. Wykonano następujące próby kontrolne: siady z leżenia, test coopera, bieg wahadłowy 4x10 m, rzut piłką lekarską znad głowy, strzał w poprzeczkę z linii 16 metrów. Badania kontrolne wykonano na początku (Pomiar I) i na końcu (Pomiar II) pierwszej rundy rozgrywek. Po pierwszej rundzie rozgrywek zaobserwowano nieistotną statystycznie poprawę wszystkich mierzonych parametrów. Istotne statystycznie różnice stwierdzono jedynie między liczbą celnych strzałów w poprzeczkę przed treningiem w pomiarze I a liczbą strzałów po treningu w pomiarze II. Abstract The aim of the study was to compare the changes in selected motor abilities, including shot accuracy, of soccer players during first round of competition. Thirteen football players from the club "Polonia" Bydgoszcz took part in the research. Characteristics of the subjects: age 24.9 ± 6.4 years, body height 177.5 ± 4.8 cm, body weight 76.2 ± 8.8 kg, training experience 15.5 ± 6.6 years. The following tests were performed: sit-ups, Cooper test, 4 x 10 m shuttle run, throw a medical ball from the head, shooting at the crossbar from the 16 m line. Control tests were conducted at the beginning (Measure I) and at the end (Measure II) of the first round. After the first round of the tournament, all the measured parameters were statistically insignificant. Significant statistically significant differences were found only between the number of shots fired at the bar before training in I measurement and the number of shots after training in measurement II.